Peningkatan Hasil Belajar Kimia Siswa Kelas XI IPA 4 SMAN 4 Pandeglang Tahun Pelajaran 2020/2021 Melalui Penerapan Model PP (Problem Posing) Berdasarkan Gaya Kognitifnya - Roslita, Ita (MENDIDIK: Jurnal Kajian Pendidikan dan Pengajaran, 2023)
This research aims to increase learning activities, improve the learning outcomes of students who have a field independent cognitive style and improve the learning outcomes of students who have a field dependent cognitive style on acid-base solution material in chemistry subjects through the application of the PP learning model. The research was carried out in two cycles, each cycle consisting of planning, implementation, observation and reflection. In cycle I, the percentage of student learning activities, the average learning outcomes and frequency of completion as well as the percentage of student understanding have not reached the target, the results of reflection must be made several improvements in cycle II by increasing apperception, motivation and appreciation as well as more guidance and attention for groups of students field dependent, and the results have been a significant increase in: student learning activities from 67.69% to 79%. The percentage of understanding of the field independent student group from 59% to 82%, the average learning outcome score in pre-cycle was 56.56, cycle I 69.13 and cycle II 81.13 with a frequency of completion from 8% to 54% to 83%. As well as the percentage of understanding for the field dependent student group from 42% to 72%, the average learning outcome score in pre-cycle was 43.21, cycle I 59.58 and cycle II 74.50 with a frequency of completion from 0% to 33% to 67%. The results of this research are: (1) The application of the PP model learning can increase student learning activities (2) The application of the PP model learning can improve the learning outcomes of field independent students (3) The application of the PP model learning can improve the learning outcomes of field dependent students on acid solution subject matter bases in chemistry subjects in class XI IPA 4 SMAN 4 Pandeglang 2020/2021 Academic Year.